Riviera Towns - Gibbons, Herbert Adams, 1880-1934; Hornby, Lester G. (Lester George), 1882-1956 (Salt Lake City, UT : Project Gutenberg, 2007)
"Riviera Towns" by Herbert Adams Gibbons is a travelogue written in the early 20th century. The book explores various picturesque towns along the French Riviera, capturing their distinct atmospheres, landscapes, and cultural essence. Through the lens of the author and his companion, the Artist, the narrative unfolds with a focus on Grasse and Cagnes, highlighting their natural beauty as well as local customs and industries. The opening of the text presents the narrator's perspective as he observes the town of Grasse from his study in Théoule, describing its allure and the missed opportunities to visit. The arrival of the Artist, fresh from New York, prompts a spontaneous trip to Grasse, where both characters engage with the town's famous perfume industry and the vibrant flora surrounding them. This interaction showcases their appreciation for beauty and nature, as well as the blend of the ordinary with the extraordinary in their explorations. Through vivid descriptions and personal reflections, the beginning sets the tone for a journey filled with artistic inspiration and cultural discovery along the Riviera. (This is an automatically generated summary.)
Release date is 2007-07-04
E-text prepared by Al Haines
Keywords: Riviera (France) -- Description and travel